Antibacterial scalarane from Doriprismatica stellata nudibranchs (Gastropoda, Nudibranchia), egg ribbons, and their dietary sponge Spongia cf. agaricina (Demospongiae, Dictyoceratida) - Hertzer, Cora (Beilstein J Org Chem, 2020)
Investigations on the biochemical relationship between Doriprismatica stellata (Chromodorididae, Doridoidea) nudibranchs, their egg ribbons, and the associated dietary sponge Spongia cf. agaricina (Demospongiae, Porifera) led to the isolation of the structurally new scalarane-type sesterterpene 12-deacetoxy-4-demethyl-11,24-diacetoxy-3,4-methylenedeoxoscalarin, with an unprecedented position of the cyclopropane ring annelated to the ring A. Unlike other scalaranes, which are most often functionalized at C-12 of ring C, it bears two acetoxy groups at C-11 and C-24 instead. The compound was present in all three samples, supporting the dietary relationship between chromodorid nudibranchs of the genus Doriprismatica and scalarane-containing dictyoceratid sponges of the Spongiidae family. The results also indicate that D. stellata passes the scalarane metabolite on to its egg ribbons, most likely for protective purposes. The scalarane showed antibacterial activity against the Gram-positive bacteria Arthrobacter crystallopoietes (DSM 20117) and Bacillus megaterium (DSM 32).